1976
DOI: 10.1002/j.1879-3479.1976.tb00578.x
|View full text |Cite
|
Sign up to set email alerts
|

Preovulatory Overripeness of the Egg in the Human Subject

Abstract: Anomalies of conception which endanger the ensuing pregnancy have been reviewed. The range of possible consequences include “occult” and early spontaneous abortions, a wide spectrum of chromosome defects, developmental anomalies, such as those of the brain (with a wide range of neuro‐psychopathology as a consequence) and possibly some other abnormalities of gestation. Pathology either of the pregnancy or of the products of conceptions caused by preovulatory overripeness ovopathy may be expected from conception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1977
1977
1988
1988

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…In one study [107], he ascertained 127 couples who had mentally retarded children, and inquired about the circumstances in which the children were conceived. After excluding couples in which the child had a known 'genetic' or 'metabolic' defect, there remained 49 couples who experienced unintended pregnancies while practicing rhythm (calendar method in all except 2 cases).…”
Section: Human Studiesmentioning
confidence: 99%
“…In one study [107], he ascertained 127 couples who had mentally retarded children, and inquired about the circumstances in which the children were conceived. After excluding couples in which the child had a known 'genetic' or 'metabolic' defect, there remained 49 couples who experienced unintended pregnancies while practicing rhythm (calendar method in all except 2 cases).…”
Section: Human Studiesmentioning
confidence: 99%
“…A number of well-documented observations are on record which indicate that characteristic seasonal fluctuations in ovulation (50), conception (8,20,35,63,74,96), abortion (7,21,59) and birth rates (19) and in the incidence of birth defects (4,22,28,45,48,51,58,62,95) exist in virtually all populations investigated. In summarizing the available data, it was demonstrated that in the northern half of Europe ovulation and conception rates showed a major rise in the spring and a minor increase in the fall with declines in the summer and winter.…”
Section: Discussionmentioning
confidence: 99%
“…Jongbloet [60] further claimed that areas of Europe having predominantly Catholic populations had a higher incidence of both anencephaly and Down syndrome. Such a claim fails to take into account genetic factors and other variables.…”
Section: Aging Gametes In Humans: Circumstantial Evidence Relatimentioning
confidence: 98%
“…Jongbloet and colleagues [59][60][61] have published several studies relating directly or indirectly to NFP populations. In our opinion, all these studies are characterized by potential pitfalls.…”
Section: Aging Gametes In Humans: Circumstantial Evidence Relatimentioning
confidence: 99%
See 1 more Smart Citation